Crisis as opportunity. Intellectuals and State in México (1934-1950) - Girola, Lidia (Tempo Social, 2016)
The purpose of this paper is to give an overview of the political and intellectual context during the formative years of both the Mexican state and some important institutions and cultural enterprises after the Mexican Revolution. I will explain the relationship between three different governments and different intellectual groups of this historical period, as well as the role that these groups played in the creation of the Fondo de Cultura Económica, the journal Cuadernos Americanos, and the journal Revista Mexicana de Sociología. I will also explain the profound interdependence of  Post-Revolutionary governments  and the participation of intellectuals in academic, technical and political positions. This is characteristic of Mexico and differentiates Mexico from other countries in Latin America.